A Critical Study of Stephen Hawking’s View of about the Inseparability Between “Cosmic Temporal of Beginningless” and “Atheism” Based on the Principles of Transcendent Theosophy - Ahmad Mansouri Matak (gilani); Fahimeh Shariʿati; Sayyid Majid Saberi Fathi (آموزه‌‌های فلسفه اسلامي)
The issue of the temporal beginning of the cosmos is one of the challenging issues which, in addition to philosophy and theology, has attracted the attention of contemporary physicists, so that some of them have expressed metaphysical-theological reactions and even atheistic opposing in choosing their opinions. Reviewing of Stephen Hawking’s works shows that he merely bases the physical rules that rely on the method of sensation and experience without the use of metaphysical and philosophical methods. Some metaphysical results such as temporal of beginningless have concluded the creation of cosmic and thereby denied the existence of God. The findings of the research in the present article which has been written by descriptive-analytical method and with philosophical approach indicate that Hawking’s cosmic temporal of beginningless is consistent with the view of some philosophers such as Mullā Ṣadrā but Mullā Ṣadrā unlike Hawking does not conclude atheism and atheistic readings from cosmic temporal of beginningless. Some of Hawking’s ontological concepts have led to fallacy of non-sequitur and lead to internal contradictions in philosophical discussions which in this article have been investigated and evaluated with the principles and fundamentals of transcendent theosophy or al-ḥikmat al-muta’āliyah (Arabic: الحکمة المتعالیة). It has been concluded in the end that Mullā Ṣadrā considers the criterion of the cosmic need for cause as “possible” in transcendent theosophy and has concluded between the “cosmic temporal of beginningless” and “the existence of God.”